PERFORMANCE EVALUATION OF RESILIENT MODULUS AND FATIGUE RESISTENCE USING EAF SLAG AGGREGATES IN ASPHALT CONCRETE BINDER COURSE WARM MIX MIXTURE (WMA AC-BC) - Natalia Situmorang, Astri
Sustainable infrastructure supported by balancing between fulfill the needs of the present and the future. Two main aspects is the environmental and resource aspects. EAF Slag Aggregate is a steel waste which used as alternative aggregate that supports the resource aspects. While Zeolit Aspha-Min is a Warm Mix additive that supports reducing CO2 gas emissions and greenhouse gases in environmental aspects This study observed performance of warm asphalt mixture (WMA AC-BC) with replacement of 30% EAF Slag Aggregate toward natural aggregates. Whereas Aspha-Min zeolite content based on previous studies were mixed with 0.3% and 0.5% towards weight of mixture. The mixing and compaction temperature of Warm- Mix were obtained by trial and error 100C - 200C below the asphalt viscosity temperature. The mixtures contained of 0.3% Aspha-Min levels can reduce mixing temperatures and compaction up to 200C. It is more resistant to fatigue but has the lowest resilient modulus value than the other mixtures. While The mixtures contained of 0.5% Aspha-Min can reduce the mixing temperature and compaction up to 100C. This mixture tends to be more stiff because it has the highest resilient modulus value and has a low Nf cycle value that is susceptible to fatigue compared to other mixtures. The optimum mixture was obtained from the proportion of 30% Slag EAF mixture with the addition of 0.3% Aspha-Min additive in terms of reducing mixing compacting temperature and resistance to fatigue.